A modified quantum-based particle swarm optimization for engineering inverse problem. Issue 1 (3rd January 2017) - Rehman, Obaid Ur; Yang, Shiyou; Khan, Shafi Ullah
Abstract : Purpose: The purpose of this paper is to explore the potential of standard quantum-based particle swarm optimization (QPSO) methods for solving electromagnetic inverse problems. Design/methodology/approach: A modified QPSO algorithm is designed. Findings: The modified QPSO algorithm is an efficient and robust global optimizer for optimizing electromagnetic inverse problems. More specially, the experimental results as reported on different case studies demonstrate that the proposed method can find better final optimal solution at an early stage of the iterating process (uses less iterations) as compared to other tested optimal algorithms. Originality/value: The modifications include the design of a new position updating formula, the introduction of a new mutation strategy and a dynamic control parameter to intensify the convergence speed of the algorithm.